2014
DOI: 10.3389/fsurg.2014.00024
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis and Infertility: How and When to Treat?

Abstract: Endometriosis is defined as the presence of endometrial-like tissue (glands or stroma) outside the uterus, which induces a chronic inflammatory reaction. Although endometriosis impairs fertility, it does not usually completely prevent conception. The question of evidence based-medicine guidelines in endometriosis-associated infertility is weak in many situations. Therefore, we will highlight in this issue where the challenges are.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 58 publications
0
49
0
4
Order By: Relevance
“…Patient-derived endometrial organoids can also be exploited for modeling endometriosis, a disease that affects between 10 and 15% of all women of reproductive age and 70% of women with chronic pelvic pain (Giudice and Kao, 2004;Vercellini et al, 2013). When one considers that there is no curative solution for endometriosis (Fadhlaoui et al, 2014), it is hoped that endometrial organoids may help to accelerate the development of novel therapeutics in this area of research.…”
Section: Advantages and Applications Of Endometrial Organoidsmentioning
confidence: 99%
“…Patient-derived endometrial organoids can also be exploited for modeling endometriosis, a disease that affects between 10 and 15% of all women of reproductive age and 70% of women with chronic pelvic pain (Giudice and Kao, 2004;Vercellini et al, 2013). When one considers that there is no curative solution for endometriosis (Fadhlaoui et al, 2014), it is hoped that endometrial organoids may help to accelerate the development of novel therapeutics in this area of research.…”
Section: Advantages and Applications Of Endometrial Organoidsmentioning
confidence: 99%
“…Recent reports have indicated that infertility was due to the presence of endometriosis for 20-50% of infertile couples [3][4][5], and endometriosisrelated infertility has become a common finding among infertility patients. Infertility patients with endometriosis are treated in accordance with the clinical ESHRE guidelines [4] or expert opinion [6]. Although these guidelines were established based on the literature data, such as the Cochrane review [7], they fail to describe the duration between surgical treatment for endometriosis and the establishment of the first pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Endometriosis is a complex and multifactorial disease and its etiology and pathogenesis have not yet been completely clarified [8].…”
Section: Pathogenesismentioning
confidence: 99%